A Novel Mutation in the NBD Domain of NLRC4 Causes Mild Autoinflammation With Recurrent Urticaria - Wang, Li; Wen, Wen; Deng, Mengyue; Li, Yue; Sun, Gan; Zhao, Xiaodong; Tang, Xuemei; Mao, Huawei (Frontiers in Immunology, 2021)
Background: NOD-like receptor family CARD-containing 4 protein (NLRC4) is a cytosolic protein that forms an inflammasome in response to flagellin and type 3 secretion system (T3SS) proteins from invading gram-negative bacteria. NLRC4 mutations have been recently identified in early-onset severe autoinflammatory disorders. Here, we report a novel mutation in NLRC4 in two Chinese patients in one family, who manifested with recurrent urticaria and arthralgia. Cases: We sought to identify a genetic cause of a disease for two patients in one family. Both of them presented with recurrent urticaria and arthralgia. Methods: We summarize the clinical data of the two patients in one family. Gene mutations were identified by whole-exome sequencing (WES). Swiss-PdbViewer was used to predict the pathogenicity of identified mutations. Cytokin levels and caspase-1 activity were detected in the patient PBMC under lipopoly-saccharide (LPS) stimulation. All published cases with NLRC4 mutation were reviewed. Results: We identifified a missense heterozygous mutation (c.514G>A, p.Gly172Ser), which was revealed in the highly conserved residue of nucleotide-binding domain (NBD) of NLRC4. The mutation did not alter the expression of NLRC4 protein, but induced much higher production of IL-1β and IL-6 in patients’ PBMC compared to that in health control upon LPS stimulation. Four NLRC4 inflammasomopathy phenotypes have been described, which showed severe inflammatory diseases including macrophage activation syndrome, enterocolitis and NOMID in patients with mutation in the NBD and HD1 domains, whereas mild clinical phenotype associated with two mutations in WHD domain of NLRC4. Conclusion: we identified a novel mutation in the NBD domain, while the patients just presented with mild inflammatory phenotype. Thus, our findings reinforce the diversity in NLRC4 mutations and expand the clinical spectrum of disease associated.